2007
DOI: 10.1590/s1413-86702007000400007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dengue on liver function as evaluated by aminotransferase levels

Abstract: The objective of this study was to evaluate the impact of dengue virus infection on liver function by measuring aminotransferase in blood samples from patients serologically diagnosed by according to two MAC-ELISA protocols. Degrees of liver damage were classified according to aminotransferase levels: grade A -normal enzyme levels; grade B -increased levels of at least one of the enzymes; grade C -increased, with at least one of the enzymes being at levels higher than three times the upper reference values; gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 11 publications
6
52
0
3
Order By: Relevance
“…In relation with the clinical manifestation investigation, which could be associated with hepatic function disorders (nausea and vomiting, abdominal pain and hepatomegaly), there were no significant differences among those patients with altered enzymes (AST and ALT) and those who had enzyme dosage within the normal range. These results agree with those observed in other studies 1,4,[11][12][13] .…”
Section: Serology Resultssupporting
confidence: 94%
“…In relation with the clinical manifestation investigation, which could be associated with hepatic function disorders (nausea and vomiting, abdominal pain and hepatomegaly), there were no significant differences among those patients with altered enzymes (AST and ALT) and those who had enzyme dosage within the normal range. These results agree with those observed in other studies 1,4,[11][12][13] .…”
Section: Serology Resultssupporting
confidence: 94%
“…Our laboratory data showed that the percentage of dengue patients with mean elevated level of Aspartate transaminase and Alanine transaminase were significantly higher than that of laboratory dengue negative patients. Previous studies suggested that liver injury is a common finding in dengue infections and it is mediated by direct infection of hepatocytes and Kupffer cells (Murgue et al, 1999;Souza et al, 2007). Recently, Luiz et al suggested the use of markers such as Aspartate transaminase and Alanine transaminase as parameters to evaluate severity in patients with dengue fever (Luiz et al, 2004).…”
Section: Journal Of Virology and Microbiologymentioning
confidence: 99%
“…Upon admission, the levels of AST, ALT, and serum alkaline phosphatase were elevated in 87% of children with hepatomegaly and in 81% of children without hepatomegaly. Hepatic dysfunction is a well-recognized feature of dengue infection and often manifests as hepatomegaly and mild to moderate increases in transaminase levels; jaundice and acute liver failure generally occur less commonly 14 . Kabra et al 11 evaluated 240 children aged between 4 months and 13 years who were admitted to a hospital in India with a clinical diagnosis of dengue infection.…”
mentioning
confidence: 99%